Dakwah Wasathiyah Al-Islam Melalui Penyuluh Agama Islam di Kota Surakarta - Asmara, Arif Yudi (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
The concept of wasathiyah al-Islam is an important concept for the Islamic world today. Especially for the development of the da’wah method which metamorphosed into Da’wah wasathiyah al-Islam. Understanding Da’wah wasathiyyah al-Islam: ’is (justice), at-tawazun (balance), and tasamuh (tolerant) in religion is the responsibility of Islamic da’wah, including Islamic Religious Counselors, especially in Surakarta City. Functional Islamic Religious Extension is the main task to provide guidance or counseling and development in the language of religion. Surakarta is a barometer of various religious sects and schools ranging from radicalism, Wahhabism, liberalism is a challenge for Islamic Religious Extension, especially during this Covid 19 pandemic. Wasathiyah da’wah plays an active role in changing the mindset of the target group in responding to differences from one another, such as not highlighting differences in carrying out religious teachings, conducting joint recitations, and carrying out religious activities together, are indicators of the success of wasathiyah al-Islam da’wah.